2022
DOI: 10.1007/s11255-022-03250-0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse upgrading and/or upstaging in contemporary low-risk prostate cancer patients

Abstract: Background Upgrading and/or upstaging in low-risk prostate cancer (PCa) patients may represent an indication for active treatment instead of active surveillance (AS). We addressed contemporary upgrading and/or upstaging rates in a large population based-cohort of low-risk PCa patients. Materials and methods Whitin the SEER database (2010–2015), NCCN low-risk PCa patients were identified across management modalities: radical prostatectomy (RP), radiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…In accordance with the aforementioned, we observed a high prevalence of adverse features within our cohort. The rate of upstaging/upgrading stood at 33%, similar to contemporary series (ranging from 24.8% to 45%) [ 17 , 18 ]. Furthermore, most ECE cases presented a non-focal extension.…”
Section: Discussionsupporting
confidence: 78%
“…In accordance with the aforementioned, we observed a high prevalence of adverse features within our cohort. The rate of upstaging/upgrading stood at 33%, similar to contemporary series (ranging from 24.8% to 45%) [ 17 , 18 ]. Furthermore, most ECE cases presented a non-focal extension.…”
Section: Discussionsupporting
confidence: 78%
“…In prostate cancer, the discrepancy between the biopsy Gleason score and the radical prostatectomy (RP) Gleason score is a well-known phenomenon [1][2][3][4][5][6][7][8]. In particular, upgrading has been thoroughly studied in several single-and multi-institutional, as well as population-based databases [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have shown that in approximately half of patients, tumor grades reported in diagnostic biopsies are lower than those determined in prostatectomy specimens. 11,20,21 This is of vital importance in terms of active surveillance (AS) and/or the timely evaluation of curative treatment options, especially in patients diagnosed at an early age. 24 Although there are studies in the literature on the parameters that can predict a histological upgrade, clear conclusions that can guide the clinical approach have not yet been reached.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] It has been reported that the histological grade of the tumor increases in approximately half of patients who have undergone Rp compared to their diagnostic prostate biopsies. 11,20,21 In these patients, there is an increase in disease recurrence rates after prostatectomy and the need for additional oncological treatment. 22 Although there are some studies in the literature investigating parameters that can predict an increase in histological grade, such as age at the time of diagnosis, serum PSA and PSA density values, prostate volume, the number of tumor-positive cores in biopsies, and tumor quantification), it is not yet possible to draw clear conclusions that can guide the clinical approach in this field.…”
Section: Introductionmentioning
confidence: 99%